1973
DOI: 10.1901/jaba.1973.6-277
|View full text |Cite
|
Sign up to set email alerts
|

SELF‐EVALUATION BY ADOLESCENTS IN A PSYCHIATRIC HOSPITAL SCHOOL TOKEN PROGRAM1

Abstract: Nine adolescent boys with a history of high rates of disruptive classroom behavior were selected from a psychiatric hospital school and placed in a remedial reading class after school in which various factors in a token reinforcement program involving self-evaluation were investigated. The effects of self-evaluation, in the form of a rating the students gave themselves about the appropriateness of their classroom behavior, were first assessed. While the students' ratings of their own behavior correlated highly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
33
0

Year Published

1974
1974
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(37 citation statements)
references
References 15 publications
4
33
0
Order By: Relevance
“…They were able to attend to more instructional and individual-oriented organizational duties. This supported the assertion of Santogrossi et al (1973) that the removal of control responsibilities allows an educator to devote more energy to creative instruction.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…They were able to attend to more instructional and individual-oriented organizational duties. This supported the assertion of Santogrossi et al (1973) that the removal of control responsibilities allows an educator to devote more energy to creative instruction.…”
Section: Discussionsupporting
confidence: 63%
“…It would seem that the characteristics of publicly self-recording performance progress in both work output and attendance is a durable reinforcing process. Santogrossi et al (1973) expressed some doubts as to the perseverency of self-reinforcing effects, as the studies they reviewed were conducted over relatively short periods of time. This investigation evidenced the long-lasting effects of the self-evaluation procedures when used with normal subjects.…”
Section: Discussionmentioning
confidence: 99%
“…In the classroom setting, Bolstad and Johnson (1972), Drabman, Spitalnik, andO'Leary (1973), Glynn et al (1973), and Kaufman and O'Leary (1972) reported successful behavior maintenance capacities of self-reinforcement procedures when applied after periods of behavior modification by usual external reinforcement procedures. However, Santogrossi, O'Leary, Romanczyk, and Kaufman (1973) While these within-lesson changes in appropriate behavior can be handled by trained observers, they present problems to young children assessing their behavior and self-administering reinforcement. A child listening to a teacher's instruction in the middle of a written expression lesson might rate himself as off-task because he was not writing at the moment he had to assess his own behavior.…”
mentioning
confidence: 99%
“…Observation has involved a variety of methods, induding time sampling (e.g., Greene et al, 1976;Montegar, Reid, Madsen, & Ewell, 1977), interval recording 119 1991124,119-127 NUMBER 1 (SPRING 199 1) (e.g., Katz, Johnson, & Gelfand, 1972), behavior inventories (e.g., Pomerleau, Bobgrove, & Smith, 1973), and outcome observations (e.g., . Other researchers have reduced the time required to conduct these observations by using staff self-reports (e.g., Santogrossi, O'Leary, Romanczyk, & Kaufman, 1973). Burg, Reid, and Lattimore (1979) used supervisors to observe independently the performance of staff members making self-reports.…”
mentioning
confidence: 99%